2018
DOI: 10.1186/s13601-018-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Diverse expression of TNF-α and CCL27 in serum and blister of Stevens–Johnson syndrome/toxic epidermal necrolysis

Abstract: BackgroundThe pathogenesis of Stevens–Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) is not fully understood. Our previous study reported that chemokine CCL27 was overexpressed in serum of SJS/TEN patients. The objective of this study was to investigate the levels of CCL27 and TNF-α in serum and blister fluid from patients with SJS/TEN during the acute stage or resolution phase.MethodsA total of 27 patients with SJS/TEN and 39 healthy donors were recruited to the study. Serum and vesicular levels of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 34 publications
2
16
1
2
Order By: Relevance
“…Although some studies have shown that serum TNF-a levels increase during the progressive stage of SJS/TEN and decrease after treatment with TNF-a inhibitors, 5 our previous study demonstrated that a high level of TNF-a could persist until the resolution stage. 13 Moreover, Berthold et al 14 More interestingly, the TNF-a-IL-6 axis has been demonstrated to be involved in several inflammatory conditions, and TNF-a blockade has been shown to decrease the level of IL-6, 15 which is consistent with our observation. Taken together, the roles of IL-6 and TNF-a in the pathogenetic mechanism underlying ILD associated with SJS/TEN is an exciting area of further inquiry.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although some studies have shown that serum TNF-a levels increase during the progressive stage of SJS/TEN and decrease after treatment with TNF-a inhibitors, 5 our previous study demonstrated that a high level of TNF-a could persist until the resolution stage. 13 Moreover, Berthold et al 14 More interestingly, the TNF-a-IL-6 axis has been demonstrated to be involved in several inflammatory conditions, and TNF-a blockade has been shown to decrease the level of IL-6, 15 which is consistent with our observation. Taken together, the roles of IL-6 and TNF-a in the pathogenetic mechanism underlying ILD associated with SJS/TEN is an exciting area of further inquiry.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, unlike IL‐6, the serum TNF‐α level continued to increase after the initiation of etanercept treatment in our patient. Although some studies have shown that serum TNF‐α levels increase during the progressive stage of SJS/TEN and decrease after treatment with TNF‐α inhibitors, our previous study demonstrated that a high level of TNF‐α could persist until the resolution stage . Moreover, Berthold et al .…”
Section: Discussionmentioning
confidence: 63%
“…TNF-α can interact with a surface death receptor TNF receptor-1, which will induce the recruitment of adaptor proteins such as FADD to trigger the extrinsic apoptotic pathway, leading to cell death. Plenty of studies support that TNF-α is strongly expressed in SJS/TEN lesions and is involved in the epidermal necrosis ( Caproni et al, 2006 ; Neuman and Nicar, 2007 ; Wang et al, 2018b ). Excitingly, TNF-α antagonists are translated into clinical therapeutics for SJS/TEN in recent years.…”
Section: T-cell-mediated Apoptosis Signaling Pathways In Sjs/tenmentioning
confidence: 99%
“…“Phenotypes” are external manifestations of asthma that result from the combination of hereditary and environmental influences [ 3 , 7 , 68 ], and which may occur in varying combinations [ 5 , 69 , 70 ] and even concurrently [ 71 ]. Furthermore, asthma phenotypes are not associated with a specific underlying pathophysiological mechanism, since different mechanisms may lead to the same phenotypic features, particularly in clinical terms [ 5 , 68 , 69 , 70 , 72 ].…”
Section: Phenotypes and Endotypes In Adult Asthmamentioning
confidence: 99%